PENGARUH INDEPENDENSI DEWAN KOMISARIS, KONEKSI POLITIK, UKURAN PERUSAHAAN, PROFITABILITAS, DAN LEVERAGE TERHADAP PENGHINDARAN PAJAK PADA PERUSAHAAN INDEX BEI SUB KLASIFIKASI GROWTH/VALUE - Amnar, Harve; Pasaribu, Aria Masdiana; Muhajir, Ahmad; Silalahi, Alistraja Dison (Fakultas Ekonomi Universitas Al-Azhar Medan, 2024)
This research investigates factors that influence corporate behavior in tax compliance by using a quantitative approach to analyze companies from various industries listed on the IDX Growth/Value sub-classification. The multiple linear regression analysis determines the strength and significance of relationship between the variables studied. The research population was taken from the IDXG30 and IDXV30 indices which contained 88 enterprieses from 2019 until 2021 with the amount of sample size of 45. The results of this research showed that the independence of the board of commissioners and political connections had a practical and a noteworthy impact on tax evasion. Meanwhile, size of firm, profitability and leverage demonstrate a strong and negative correlation with tax evasion. Overall, the factors studied show a significant influence on tax avoidance